PROCESSING OF URANIUM WASTE USING ALUMINA SILICA PHOSPHATE - Aisyah Aisyah; Herlan Martono; Wati Wati (Institut Teknologi Bandung, 2008)
Uranium waste generated from the utilization of nuclear technology on radioisotope production, nuclear fuel production, calibration of fuel post-irradiation, and the purification of uranium from yellow cake. Uranium is a long-lived radionuclides and hazardous if it was entered in human body, thus requiring appropriate treatment with high safety. The processing conducted by separated the uranium which was contained on waste with ions exchange process. Uranium has been separated, later then immobilized with the polymer. The study of simulation uranium waste processing using an Alumina Silica Phosphate (ASP) has been conducted. Simulation uranium waste with the concentration of 0,05 g/l was contacted to ASP with contact timer and pH as a parameters. The Alumina Silica Phosphate which saturated with uranium, later then immobilized with epoxy resin polymer by total of waste contents as a parameter. The immobilization was conducted by mixing ASP which saturated with uranium and epoxy resin. The study showed that the best composition of ASP was obtained at the ratio of 1:1, contact time of 15 minute, and pH of 7 with absorption of uranium about 93,5%. The characteristic of polymer and the immobilization waste showed that optimum of waste content is 20% of weight with the density of 1,0538 g/cm3; compressive strength of 19,96 kN/cm2 and there was not detected the leaching of uranium which out from the polymer-waste. Therefore, ASP can be used on processing of uranium waste and could be suggested to be applied on Radioactive Waste Management Installation.